The Human-Space Relationship in Barrio Mugica (Villa 31) of Buenos Aires: The Necessity of Human Habitation (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2025)
This study concerns the relationship between man and space in Barrio Padre Carlos Mugica, formerly Villa 31 of Buenos Aires, which can be traced back to the human need to inhabit the world. The relationship between man and space is the root of all Villas in Buenos Aires and Argentina. It is a relationship based on the human-space continuity, the human need to live and inhabit space, and therefore the innate tendency to carve out space within space to inhabit the world. Barrio Mugica is a unique and particular space. It is a living organism, spatial and human, spontaneous and resilient. It is a complex place in itself and, simultaneously, a space that contains and expresses the complexity of the contemporary metropolis. In Barrio Mugica, the necessity of human habitation expresses a particular relationship and a visible integration between man and space. In the need to occupy space – not only to inhabit the world but also to claim a place in it and assert oneself as a living human being – people and spaces integrate, creating human and spatial relationships, while the individual constructs a dual spatiality, both physical and mental, materialising through architectural self-construction, both their physical surroundings and their inner mental world. Spatially, Barrio Mugica has nothing to do with the peripheral spaces of large metropolises or with the margins of urban centres. Villa 31 is a space that has developed within the city, not outside or at its edges. However, it can be considered peripheral and marginal when referring to those social peripheries and marginalities that Pope Francis identifies as “existential” peripheries, where survival education prevails (Bergoglio 2015). The objective of this study is to historically and presently highlight – even through the author’s photographic reportage – the necessity of human habitation expressed in Villa 31 and the particular human-space relationship on which the Villa itself is founded. Understanding the human need to live and inhabit space and to claim a place in the world can be helpful in the future of the Villas and the people who inhabit them. Moreover, it may also be helpful in the future for expanding and rethinking perspectives and positions on the Villas for those who observe them.
Keywords: mental space; metropolis; physical space